Transforming breast health education in a society 5.0 framework - Mohd Zain, Norhayati; i Che Mut, Nur Anis Izzat; M Rosli, Nur Dini Dalilah; Mahmud, Adzmel; Nazruddin, Azlan Shah (Faculty of Medicine, 2026)
Breast health literacy, encompassing awareness of risk factors, symptom recognition, and proficiency in self-examination, is crucial for women to adopt proactive health practices that improve outcomes. Recently, digital health tools have gained prominence as innovative means to enhance health knowledge and empower individuals in managing their well-being. The Breast Imaging Education Bot (BieBot©) is an interactive chatbot created to provide detailed educational content on breast health, with a focus on breast cancer and its screening techniques. The development of BieBot© as a conversational platform reflects a progressive strategy aligned with Society 5.0 principles within healthcare. Utilizing advanced chatbot technology, this project aims to empower women by delivering accessible, trustworthy information about breast cancer and examination procedures. Methods: BieBot© supports both Malay and English languages and incorporates engaging visuals and videos consistent with guidelines from the Malaysian Ministry of Health. The content, carefully reviewed by breast cancer and imaging specialists, was pilot tested with 100 women during a breast awareness event in January 2025. Results: The responses were highly positive, with users praising its ease of use and informative nature. Participants particularly appreciated the interactive features and visual aids, which facilitated comprehension and sustained engagement. Conclusions: This innovative educational approach exemplifies the essence of Society 5.0 by enhancing digital health literacy, providing personalized learning experiences, and applying state-of-the-art technology to improve healthcare delivery and patient empowerment. Ultimately, it fosters a shift towards a human-centered, technology-enhanced healthcare system that prioritizes education, accessibility, and patient involvement.